METHODICAL DEVELOPMENT OF EXTRACURRICULAR ACTIVITIES IN PHYSICAL EDUCATION AND SPORTS - Arabjonov Shokirjon Shavkatovich (Zeta Repository, 2023)
Physical education and sports extracurricular activities are an important aspect of a student's all-round development, physical education and sports training are of great importance in providing physical and mental health to a person and in the process of studying at higher educational institutions. it is about the study of the influence of physical culture on the process of personality formation and the choice of the type of professional activity and similar information.